1982
DOI: 10.1017/s0043174500040509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shade on Silverleaf Nightshade (Solanum elaeagnifolium)

Abstract: Plants started with seed, 'seedlings', and established plants of silverleaf nightshade (Solanum elaeagnifoliumCav.) were grown in the field under shade levels of 0, 47, 63, and 92% of full sunlight to determine vegetative, reproductive, and physiological responses to shade. Dry-matter production of both 'seedling’ and established plants declined markedly with increasing shade levels. Established plants did not bear fruit under 92% shade, and 63% shade prevented fruit production by 'seedlings'. Taproots of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Other studies have also shown that shade limits sexual reproduction in both clonal (e.g. Boyd & Murray 1982; Dall'Armellina & Zimdahl 1988) and non‐clonal plants (e.g. Benvenuti et al 1994).…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have also shown that shade limits sexual reproduction in both clonal (e.g. Boyd & Murray 1982; Dall'Armellina & Zimdahl 1988) and non‐clonal plants (e.g. Benvenuti et al 1994).…”
Section: Discussionmentioning
confidence: 94%
“…While a considerable amount of research has been carried out to explore the way competition between crops and weeds affects growth responses (Patterson, 1979;Boyd & Murray, 1982;Bubar & Morrison, 1984;DeH'Armellina & Zimdahl, 1988), very little work has been done on how weed reproduction is affected (Stoller & Mayers, 1989). Analytical study of environmental factors is extremely important in investigation of weed reproduction and survival, since they influence both seed production and seed rain.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that each silverleaf nightshade plant can produce 40–60 fruits and each mature fruit contains 24–149 seeds (Boyd & Murray 1982a). The soil seed bank of silverleaf nightshade can persist for at least 10 years (Boyd & Murray 1982a). Silverleaf nightshade seedlings usually emerge after heavy rainfall between spring and autumn (Stanton et al .…”
mentioning
confidence: 99%